Formulasi Gel Antijerawat Dengan 1,5-Bis(3’-Etoksi-4’-Hidroksifenil)-1,4-Pentadien-3-On (EHP) Sebagai Bahan Antibakteri - Esti Mulatsari; Esti Mumpuni; Agus Purwanggana; Siti Marsha Dyah Kusumaningtyas (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Acne is a skin disease that causes non-inflammatory follicular papules, nodules, pustules and inflammatory papules. There are various oral and topical anti-acne preparations on the market. Gels are topical preparations that have better absorption than cream preparations. The anti-acne gel is formulated with antibacterial active compounds. The compound 1,5-bis(3’-ethoxy-4’-hydroxyphenyl)-1,4-pentadien-3-one (EHP) is one of the curcumin analogue compounds that have been successfully synthesized by Mumpuni et al, 2010. EHP has the potential to inhibit growth of pathogenic microbes such as Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli and Salmonella typhi, and has anti-inflammatory activity. This study aims to make an anti-acne gel formula with the active ingredient EHP as an antimicrobial agent. The formula was tested for physical and chemical stability including organoleptic, spreadability, homogeneity, viscosity, flow properties, microbiological activity and skin irritation ability. EHP is formulated in gel preparations in various concentrations. Stability test of gel preparations was carried out at a temperature of 40 °C; RH ± 75% for 4 weeks.The results showed that EHP can be formulated into gel preparations that meet the physical and chemical quality requirements. Gel preparations with the active ingredient EHP 0.1%; tretionine 0.01%; carbopol 940 1.0%; triethanolamine 1.0%; propylenglycol 15%; ethanol (96%) 10%; can inhibit the Propionibacterium acnes bacteria with a diameter of 19.6 mm in the inhibition area, the skin irritation test of rabbits does not cause irritation, thus the gel preparation with the active ingredient EHP is suitable to be developed as an anti-acne gel product.